Darolutamide: a novel androgen-signaling agent in nonmetastatic castration-resistant prostate cancer - Aragon-Ching, Jeanny B (Asian J Androl, 2019)
ARAMIS is an international Phase III trial demonstrating the beneficial role of darolutamide, a novel anti-androgen that has been found to prolong metastasis-free survival in men with nonmetastatic castration-resistant prostate cancer. Darolutamide is a novel nonsteroidal androgen receptor antagonist that has unique structurally distinct properties with low blood–brain barrier penetration that was shown to improve metastasis-free survival by 22 months compared to placebo (40.4 months vs 18.4 months), reducing the risk of metastasis or death by 59%. Darolutamide also showed improvement in secondary and exploratory endpoints including progression-free survival, prolonged time to PSA progression, PSA response and time to initiating additional antineoplastic therapy, time to pain progression, and time to cytotoxic chemotherapy, but overall survival is not yet reached in either the darolutamide or the placebo arm. Adverse events leading to trial discontinuation were similar at 8.9% and 8.7% in the darolutamide and placebo arms, respectively. Darolutamide was filed as a new drug application to the United States Food and Drug Administration (US FDA) for use in the setting of nonmetastatic castration-resistant prostate cancer.